Evaluasi Usability Aplikasi E Commerce UMKM menggunakan Metode System Usability Scale (SUS) - Afifah Chesa Luckytalia (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) increasingly rely on e-commerce applications to enhance business performance and broaden market access. Nevertheless, the effectiveness of such applications is strongly determined by their usability, which reflects how easily users can interact with the system. This study aims to evaluate the usability of an MSME e-commerce application using the System Usability Scale (SUS) method. A quantitative descriptive approach was applied by distributing SUS questionnaires to 30 respondents who had previously used the application. The instrument consisted of 10 standard SUS statements measured using a five-point Likert scale. Data were analyzed by calculating individual SUS scores and determining the overall average score. Based on the randomized respondent data, the application achieved an average SUS score of 80,25. This score is categorized as Excellent and acceptable. These findings indicate that the MSME e-commerce application has a very good usability level and is well accepted by users. Therefore, the application has strong potential to support MSME digitalization and improve online transaction effectiveness.